2016
DOI: 10.1111/bph.13542
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PI3K promotes dilation of human small airways in a rho kinase‐dependent manner

Abstract: Background and PurposeAsthma manifests as a heterogeneous syndrome characterized by airway obstruction, inflammation and hyperresponsiveness (AHR). Although the molecular mechanisms remain unclear, activation of specific PI3K isoforms mediate inflammation and AHR. We aimed to determine whether inhibition of PI3Kδ evokes dilation of airways and to elucidate potential mechanisms.Experimental ApproachHuman precision cut lung slices from non‐asthma donors and primary human airway smooth muscle (HASM) cells from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…One of the small-molecule compounds with a high-connectivity score was GSK-1059615, a pan PI3K inhibitor. Inhibition of PI3K has been shown to reduce airway remodeling (26,27), reduce ovalbumin-induced airway hyperresponsiveness in mice (28), and reverse carbachol-induced constriction of human airways (18). The presence of this airway-modifying drug on our list of potential compounds supported our hypothesis that connectivity mapping could be used to identify therapeutics for airway smooth muscle dysfunction.…”
Section: Loss Of Cftr Causes Differential Gene Expression In Porcine supporting
confidence: 55%
See 1 more Smart Citation
“…One of the small-molecule compounds with a high-connectivity score was GSK-1059615, a pan PI3K inhibitor. Inhibition of PI3K has been shown to reduce airway remodeling (26,27), reduce ovalbumin-induced airway hyperresponsiveness in mice (28), and reverse carbachol-induced constriction of human airways (18). The presence of this airway-modifying drug on our list of potential compounds supported our hypothesis that connectivity mapping could be used to identify therapeutics for airway smooth muscle dysfunction.…”
Section: Loss Of Cftr Causes Differential Gene Expression In Porcine supporting
confidence: 55%
“…Using this analysis, we found 9 upstream regulators that were dysregulated due to CFTR loss (Supplemental Table 3). Interestingly, many of the proposed upstream regulators, such as phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) and phosphodiesterase signaling, have been implicated in airway smooth muscle function and disease (18,19). Others, such as WNT and CREB, have been studied in CF (20)(21)(22).…”
Section: Loss Of Cftr Causes Differential Gene Expression In Porcine mentioning
confidence: 99%
“…During migration, fibroblasts adhere to the extracellular matrix (ECM) through integrin molecules and generate a single‐cell traction force (Style et al, ). We used a recently developed single‐cell contraction assay that required cell adhesion to the FLECS printed with fibronectin (Koziol‐White et al, ; Pushkarsky et al, ). The FLECS assay showed that mouse dermal fibroblasts increased the cell contraction behavior by Npas2 KO mutation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Single‐cell contraction was measured using fluorescently labeled elastomeric contractible surfaces (FLECS) (Forcyte Biotechnologies Inc., Los Angeles, CA) (Koziol‐White et al, ). FLECS plates with the soft silicone elastomer filmed bottom were micropatterned with fluorescent fibrinogen in uniform “X” shapes (70 μm diagonal by 10 μm thick).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers thus concentrate their use of these systems on the investigation of rapid (seconds to hours) or short‐term (within days) responses. In asthma research, PCLS are used extensively for the investigation of new drugs or interventions interfering with bronchial constriction . Noteworthy, carefully done studies point to remarkable differences between mice and man with respect to the regulation of bronchial constriction .…”
Section: Modeled Diseasesmentioning
confidence: 99%